A Quasi-Newton Algorithm Without Calculating Derivatives for Unconstrained Optimization (Journal of Computational Mathematics, 2021)
A new algorithm for unconstrained optimization is developed, by using the product form of the OCSSR1 update. The implementation is especially useful when gradient information is estimated by difference formulae. Preliminary tests show that new algorithm can perform well.